Enhancing steganography using modified HHO and RC4 (Nexo Revista Científica, 2023)
A lot of information is being sent around the globe these days, which increases the risk of knowledge leakage; as a result, it is crucial to preserve information security while exchanging data. Steganography and cryptography are the most essential methods, among many others, to guarantee the data's confidentiality.  Encryption is making information unintelligible to anybody but the intended recipients. However, steganography is the study of hiding information in digital media so that nobody can detect it is there. This research introduces two methods for concealing and encrypting messages that improve the Stego image's visual quality and security while offering a sizable embedding capacity.  A stream cipher method with a symmetric key, the RC4 algorithm, is utilized to encrypt and decode secret information. At the same time, a population-based metaheuristic, modified HHO, is employed to find the optimum spots in the cover medium to conceal encrypted sensitive data. Regarding security, picture quality, and attack resistance, the testing findings show that the proposed method excels over competing methods in terms of time and cost.